2020
DOI: 10.2196/24960
|View full text |Cite
|
Sign up to set email alerts
|

An Affordable, User-friendly Telerehabilitation System Assembled Using Existing Technologies for Individuals Isolated With COVID-19: Development and Feasibility Study

Abstract: Background Isolation due to a COVID-19 infection can limit activities and cause physical and mental decline, especially in older adults and people with disabilities. However, due to limited contact, adequate rehabilitation is difficult to provide for quarantined patients. Telerehabilitation technology could be a solution; however, issues specific to COVID-19 should be taken into consideration, such as strict quarantine and respiratory symptoms, as well as accessibility to deal with rapid increases … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…Our project implemented a new telerehabilitation program, following other rehabilitation areas such as neurologic, cardiac, or musculoskeletal, and has been driven by these exceptional circumstances generated by the pandemic [ 28 , 29 , 30 ]. Telerehabilitation in COVID-19 patients, which has been proposed in case series [ 16 , 31 ], presents both possible advantages and risks in large sample sizes, such as those planned in our clinical trial.…”
Section: Discussionmentioning
confidence: 99%
“…Our project implemented a new telerehabilitation program, following other rehabilitation areas such as neurologic, cardiac, or musculoskeletal, and has been driven by these exceptional circumstances generated by the pandemic [ 28 , 29 , 30 ]. Telerehabilitation in COVID-19 patients, which has been proposed in case series [ 16 , 31 ], presents both possible advantages and risks in large sample sizes, such as those planned in our clinical trial.…”
Section: Discussionmentioning
confidence: 99%
“…To face this problem, telerehabilitation has increased in importance. Indeed, it has been demonstrated that a session of exercise through a telerehabilitation system is feasible [ 12 ], and it has been proposed as a way of managing COVID-19 [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on this, it could become the therapeutic method of choice to allow the treatment and supervision of isolated patients due to infection during home confinement [15][16][17]. It has been suggested that a session of exercise through a telerehabilitation system may be a feasible option to manage quarantined patients with COVID-19 [18,19], enabling physiotherapists to provide interactive treatments by means of different devices [20].…”
Section: Introductionmentioning
confidence: 99%